Contação de histórias, brincadeiras e dramatização nas mediações pedagógicas da educação física com a educação infantil - Franco, Fernanda Mendes (2022)
This thesis discusses the pedagogical use of children’s narrated playtime activities to mediate Physical Education (PE) and Early Childhood Education (ECE) via two research methods: a bibliographic research and an existential action research. Children’s narrated playtime activities are known to bring together storytelling, dramatization, and PE. This research aimed at: a) identifying what postgraduate studies in PE in Brazil have produced on teaching practices using role-play and storytelling in ECE; b) presenting and describing an action research proposal to ECE that employs storytelling, dramatization, literature, and corporeality in PE pedagogical mediation; and c) analyzing a proposal for pedagogical mediation between PE and ECE which sought to recognize and value children's protagonism, curricular articulation, and education of ethnic-racial relations through storytelling, games, and dramatization. The bibliographic research was selected to gather knowledge on the status of Brazilian postgraduate studies’ outcomes in PE regarding teaching practices using dramatization and storytelling in ECE. The data produced through the bibliographic research came from two digital platforms: CAPES’ Catalog of Theses and Dissertations and the Brazilian Digital Library of Theses and Dissertations. Although recognized as essential languages in ECE, storytelling and drama have appeared peripherally in most works, with little discussion regarding methodological treatment and children's visibility in productions. The existential action research scaffolded a pedagogical practice that articulates PE, storytelling, and dramatization. Procedures of the existential action research included participant observation, field diary, photographs, videos, narratives, children's drawings, and the WhatsApp application. Three pedagogical principles guided the action research data analysis: children's protagonism, curricular articulation, and education of ethnic-racial relations. Children had significant experiences for their learning and socialization processes through the articulation among storytelling (from children's literature on African and Afro-Brazilian cultural themes), dramatization, and physical education (with children’s playtime and games). They actively participated in the whole process, expressing opinions and exercising agency. It was possible to establish dialogue among different types of knowledge and subjects of the school community. Such articulation was built throughout the pedagogical mediations, which strengthened the meetings. At first, teachers' participation was low, but during the proposals development, they were allured and became engaged in the research. Episodes of prejudice and resistance to ethnic-racial relations' theme emerged throughout this process, though. Therefore, the rationale for continuous work on the topic and engagement in the anti-racist struggle, bursting the folk belief that calls for celebration dates to address these issues.